Advancing digital item development in Asian assessment systems: insights from Kazakhstan's Unified National Testing - Didarbekova, Nauzhan; Sarmurzin, Yerbol; Altybaeva, Shugyla; Abdrasilov, Bolatbek; Karkenova, Aina (Frontiers in Education, 2025)
This study on the possibility of adopting a digital platform for item development in Kazakhstan's Unified National Testing (UNT) system employed a qualitative approach that incorporated both document analysis and semi-structured interviews with policymakers, item developers, and assessment experts. This study aimed to examine the current challenges, stakeholder needs, and global best practices. Thematic analysis identified issues such as fragmented workflows, limited metadata utilization, insufficient validation protocols, and security vulnerabilities in the existing system. These gaps hinder operational efficiency and raise concerns regarding test validity. The literature review and global best practices provided a hybrid framework of functional and organizational requirements for adopting digital platforms contextualized for Kazakhstan. The contributions include (1) an empirically grounded requirements specification that triangulates documentary evidence and stakeholder insights, (2) understanding the professional culture of assessment in the Central Asian context, and (3) policy recommendations for phased implementation, metadata governance, and localized platform design. The research findings and insights offer practical recommendations for policymakers and development partners involved in ecosystem assessment reform.